(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Behavioral geography is a way to deal with human geology that endeavors to comprehend human movement in space, spot, and condition by examining it at the disaggregate dimension of investigation—at the dimension of the distinct individual. Behavioral geographers break down information on the behavioral of distinct individuals, perceiving that people shift from one another. A key fundamental of behavioral geology holds that models of human movement and association can be improved by consolidating progressively practical suspicions about human behavioral.